HR 4049: A Spectroscopic Analysis of a Post-AGB Object - Shakhida T. Nurmakhametova; Nadezhda L. Vaidman; Anatoly S. Miroshnichenko; Azamat A. Khokhlov; Aldiyar T. Agishev; Berik S. Yermekbayev; Stephen Danford; Alicia N. Aarnio (Galaxies)
A new spectroscopic study of HR 4049, a post-AGB star in a binary system, based on échelle spectra taken between 2019 and 2025 with the 0.81 m telescope of the Three College Observatory (North Carolina, USA) at a resolution of R ≈ 12,000 is reported. A cross-correlation analysis of 73 spectra of a single C i multiplet in the 4760–4780 Å range yielded the following orbital parameters: the orbital period <semantics>P=428.474±0.002</semantics> days, eccentricity <semantics>e=0.29±0.01</semantics>, argument of periastron <semantics>ω=242.3∘±0.3∘</semantics>, epoch of periastron <semantics>T0=2,458,383.2±0.6</semantics>, heliocentric systemic radial velocity <semantics>γ=−30.12±0.09</semantics> km s−1, and semi-amplitude of the radial velocity curve <semantics>K1=15.52±0.13</semantics> km s−1. Phase-dependent variations of the Hα line profile indicate dynamic processes in the circumstellar environment. The luminosity of HR 4049 was refined using the Gaia EDR3 parallax (<semantics>0.71±0.10</semantics> mas), corresponding to a distance of <semantics>1397±170</semantics> pc, and the average visual magnitude in the brightest state (<semantics>mV=5.35</semantics> mag). The derived luminosity, <semantics>log(L/L⊙)=4.22±0.12</semantics>, suggests an initial mass of 3.0–4.0 <semantics>M⊙</semantics>. Analysis of the mass function and most probable orbital inclinations (60°–75°) leads to current masses of <semantics>∼0.75<mspace width="3.33333pt"></mspace>M⊙</semantics> for the primary and <semantics>0.70</semantics>–<semantics>0.82<mspace width="3.33333pt"></mspace>M⊙</semantics> for the secondary component. The results confirm the system’s long-term orbital stability and provide further insights for future research into the nature of post-AGB binaries.